Exploring the Role of Principal Appreciation and Motivation in Shaping Work Culture Among Vocational School Teachers in South Aceh, Indonesia - Rasyid, Jusnaini; Sofyan, Hizir; Usman, Nasir (Journal of Educational Management and Learning, 2025)
This study investigates the impact of principal appreciation and motivation on the work culture of vocational school teachers in South Aceh District, Indonesia. Utilizing a quantitative approach, data were collected from 113 vocational school teachers across five schools through a survey that measured three key variables: principal appreciation, principal motivation, and teacher work culture. Descriptive and inferential statistical analyses, including simple and multiple regression, were employed to determine the relationships between the variables. The results showed that both principal appreciation and motivation have a positive and significant influence on teacher work culture, explaining 11.6% of its variation individually and 34.1% when combined. These findings underscore the importance of school leadership in fostering a supportive and collaborative work environment, suggesting that principals who appreciate and motivate their teachers significantly enhance the overall work culture, which in turn contributes to improved teacher performance and educational outcomes. This research highlights the critical role of leadership in shaping a productive and engaging school culture.